2015
DOI: 10.1016/j.rpped.2014.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos metabólicos do exercício físico na obesidade infantil: uma visão atual

Abstract: OBJECTIVE: To review the current literature concerning the effects of physical exercise on several metabolic variables related to childhood obesity. DATA SOURCE: A search was performed in Pubmed/MEDLINE and Web of Science databases. The keywords used were as follows: Obesity, Children Obesity, Childhood Obesity, Exercise and Physical Activity. The online search was based on studies published in English, from April 2010 to December 2013. DATA SYNTHESIS: Search queries returned 88,393 studies based on the aforem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
16

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 38 publications
0
17
0
16
Order By: Relevance
“…In the current issue of JHGD these studies evaluate technologies that involve the improvement of health conditions and/or issues for public health investigating the health situation of the population, especially children and adolescents [8][9][10] , which corroborate the themes in the health promotion field within the context of primary care focusing on teens and their vulnerabilities [11][12][13] , nutrition and influence on child and adolescent development [14][15][16][17][18] and themes focused on translational medicine, describing results to improve the health indicators of the population [19][20][21][22] . With an emphasis on nutritional status, to highlight obesity in adolescents, Tebar et al 17 found the prevalence of abdominal obesity in adolescents in the city of Londrina, Paraná, Brazil, and its associated factors.…”
mentioning
confidence: 74%
“…In the current issue of JHGD these studies evaluate technologies that involve the improvement of health conditions and/or issues for public health investigating the health situation of the population, especially children and adolescents [8][9][10] , which corroborate the themes in the health promotion field within the context of primary care focusing on teens and their vulnerabilities [11][12][13] , nutrition and influence on child and adolescent development [14][15][16][17][18] and themes focused on translational medicine, describing results to improve the health indicators of the population [19][20][21][22] . With an emphasis on nutritional status, to highlight obesity in adolescents, Tebar et al 17 found the prevalence of abdominal obesity in adolescents in the city of Londrina, Paraná, Brazil, and its associated factors.…”
mentioning
confidence: 74%
“…Trata-se de uma intervenção competente na prevenção e no tratamento da obesidade e patologias associadas, pois permite o desenvolvimento de qualidades físicas que modificam positivamente a atividade metabólica e a composição corporal, atenuando as comorbidades associadas com a obesidade. 31…”
Section: Resistência à Insulina E Inflamaçãounclassified
“…30 Destaca-se, desta forma, os benefícios do exercício físico na regulação do perfil lipídico e também o papel atenuador dos fatores de risco que estão associados à obesidade e consequente resistência à insulina. 31 Contudo, torna-se imprescindível o estudo da fisiopatologia da resistência insulínica e da DM2 para ter condições de se trabalhar o tratamento e a prevenção da morbimortalidade, provocando assim mudanças no estilo de vida de indivíduos obesos. 23 Apesar das recomendações clinicas de tratamento da obesidade serem baseados na união de inúmeras intervenções, tais como mudança de hábitos alimentares, uso de medicamentos e prática regular de exercícios físicos, há a necessidade de se avaliar a contribuição destas possíveis formas de tratamento, tendo em vista o caráter multifatorial da obesidade e da resistência à insulina, para que se evidencie o grau de contribuição do exercício físico nestes casos.…”
Section: Considerações Finaisunclassified
“…Physical training (PT) has been used as an important tool for health promotion (Paes et al, 2015), as, with the increasing longevity of the world population, it is possible to observe the progression of the number of fractures caused by a decrease in bone mineral density Stolnicki & Oliveira (2016). This can occur due to the impairment of tissue resistance, osteopenia, and osteoporosis (NIH Consensus Development Panel on Osteoporosis Prevention, Diagnosis, and Therapy, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…GH secretion is essential for skeletal development and growth and maintenance of bone mass, since its action stimulates the growth of several tissues, such as muscle tissue, in addition to other important effects on the longitudinal growth of children and adolescents. In addition, its deficiency in adults has been associated with bone loss and an increased risk of fractures (Pagnoncelli et al, 2014).…”
Section: Introductionmentioning
confidence: 99%